Lead and Cadmium Residues in Commercial Poultry Eggs in West Java Indonesia - Ellin Harlia; Eulis Tanti Marlina; Yuli Astuti Hidayati; Reginawati Hindersah (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
Anthropogenic contamination of heavy metals in both soil and water threatens human health through the consumption of livestock products. Important heavy metal toxins, namely lead (Pb) and cadmium (Cd) are present in livestock feed and drinking water and detected in poultry meat and eggs. This study aimed to detect Pb and Cd in poultry eggs (local farms, commercial farms, quail, and ducks) that are consumed by humans almost every day and considered a source of pollution in the environment farm. This research was exploratory research using the survey method and the samples were drawn randomly. The data were analyzed descriptively by calculating the mean of the heavy metal content of Pb and Cd in the samples studied and then compared with the Maximum Residue Limit of Pb and Cd recommended by the Food and Drug Supervisory Agency of the Republic of Indonesia No. 5/2018. The results showed that Pb content in poultry eggs exceeded the Maximum Residue Limit, which was 0.2500 mg/kg except for Pb content in duck eggs and Cd content in poultry eggs in which the samples were below the Maximum Residue Limit.